2010
DOI: 10.1111/j.1365-2966.2010.17263.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale phenomenology of the cosmic web

Abstract: We analyse the structure and connectivity of the distinct morphologies that define the cosmic web. With the help of our multiscale morphology filter (MMF), we dissect the matter distribution of a cosmological λ cold dark matter N‐body computer simulation into cluster, filaments and walls. The MMF is ideally suited to address both the anisotropic morphological character of filaments and sheets, and the multiscale nature of the hierarchically evolved cosmic matter distribution. The results of our study may be su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
264
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(299 citation statements)
references
References 107 publications
(184 reference statements)
35
264
0
Order By: Relevance
“…We need to study the morphology and galaxy populations of a larger sample of superclusters to find out whether the differences between galaxy populations in superclusters are also related to their different morphology. Aragón-Calvo et al (2010) recently studied the structure and morphologies of elements that define the cosmic web with the Multiscale Morphology Filter and data from ΛCDM simulations. The authors found several typical morphologies for filaments, which they describe as line, grid, star, and complex filaments.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We need to study the morphology and galaxy populations of a larger sample of superclusters to find out whether the differences between galaxy populations in superclusters are also related to their different morphology. Aragón-Calvo et al (2010) recently studied the structure and morphologies of elements that define the cosmic web with the Multiscale Morphology Filter and data from ΛCDM simulations. The authors found several typical morphologies for filaments, which they describe as line, grid, star, and complex filaments.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Other evidence about the influence of the largescale environment of galaxies on their properties comes from the study of the properties of galaxies in void walls (Ceccarelli et al 2008) and from the study of the large-scale environment of quasars (Lietzen et al 2009). A detailed information on the morphology of superclusters is needed to find out whether that may also be an important environmental factor in shaping the properties of galaxies and groups of galaxies in superclusters (see also Aragón-Calvo et al 2010). Einasto et al (2007d) showed that the morphology of a typical poor supercluster can be described as a "spider" -a system of several filaments growing from one concentration centre (a rich cluster).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stoica et al 2010;Bond et al 2010;Aragón-Calvo et al 2010). Many of the algorithms make use of the fact that filaments are the bridges that connect systems of galaxies (Pimbblet et al 2004;Pimbblet 2005;Colberg et al 2005;González & Padilla 2010;Smith et al 2012;Zhang et al 2013;Alpaslan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Information about the shapes of the structures found in the datasets is beyond the scope of this work; we refer the interested reader to recent excellent studies by, e.g., Jasche et al (2010), Aragón-Calvo et al (2010) and Sousbie et al (2009).…”
Section: Introductionmentioning
confidence: 99%